Effect of Low Temperatures on Biologically Active Compounds of Human Umbilical Cord Wharton's Jelly - Horbatovska, Daria S.; Falko, Oksana V.; Terekhova, Olena O.; Prokopyuk, Volodymyr Yu. (Problems of Cryobiology and Cryomedicine, 2017)
Probl Cryobiol Cryomed 2017; 27(2):182.